Surgical repair of a giant pulmonary artery aneurysm that caused severe left bronchial obstruction. (8th June 2020) - Nagato, Hisao; Nishiwaki, Noboru; Kaneda, Kozo; Tamura, Nobushige
Abstract: A 63-year-old woman on oral steroids for systemic lupus erythematosus presented with a giant pulmonary artery aneurysm severely compressing the left main bronchus and lung. Her presenting symptom was severe respiratory distress. Surgical graft replacement of the main and branch pulmonary arteries was performed, and her respiratory function improved dramatically. Bronchial obstruction was resolved immediately after the procedure.